2013
DOI: 10.1021/ma3021147
|View full text |Cite
|
Sign up to set email alerts
|

Phase Separation in the Melt and Confined Crystallization as the Key to Well-Ordered Microphase Separated Donor–Acceptor Block Copolymers

Abstract: Microphase-separated donor–acceptor block copolymers have been discussed as ideal systems for morphology control in organic photovoltaics. Typical microphases as known from coil–coil systems were not observed in such systems due to crystallization dominating over microphase separation. We show how this problem can be overcome by the synthesis of high molecular weight block copolymers leading to a high enough χN parameter and microphase separation in the melt. A combination of copper-catalyzed azide-alkyne clic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 43 publications
(85 reference statements)
5
77
0
1
Order By: Relevance
“…304 Recently, Thelakkat, Thurn-Albrecht, and co-workers have revealed the synthesis of donor−acceptor poly(3-hexylthiophene)-block-poly PBI acrylate (P3HT-b-PPerAcr) (3-51) and observed the microphase separation in melt and in subsequent confined crystallization without morphology change. 305 These crystalline liquid-crystalline, donor−acceptor diblock copolymers exhibited lamella and cylindrical phase separated structures depending on molecular weight and volume ratio between the two blocks analogous to amorphous coil−coil systems ( Figure 32). The charge transport properties of different morphologies in thin film were also investigated for these copolymers.…”
Section: Self-assembly Of Dye Arrays Composed Of Multiple Pbismentioning
confidence: 99%
“…304 Recently, Thelakkat, Thurn-Albrecht, and co-workers have revealed the synthesis of donor−acceptor poly(3-hexylthiophene)-block-poly PBI acrylate (P3HT-b-PPerAcr) (3-51) and observed the microphase separation in melt and in subsequent confined crystallization without morphology change. 305 These crystalline liquid-crystalline, donor−acceptor diblock copolymers exhibited lamella and cylindrical phase separated structures depending on molecular weight and volume ratio between the two blocks analogous to amorphous coil−coil systems ( Figure 32). The charge transport properties of different morphologies in thin film were also investigated for these copolymers.…”
Section: Self-assembly Of Dye Arrays Composed Of Multiple Pbismentioning
confidence: 99%
“…Compared with the p-type block copolymers, relatively few results are available for n-type block copolymers, possibly due to the difficulty of the synthetic method based on n-type conjugated backbones. [143][144][145][146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161] However, a study on donor-acceptor rod-coil diblock copolymers of P3HT and poly(2-phenyl-5-(4-vinylphenyl)-1,3,4-oxadiazole) (POXD) showed that the incorporation of the POXD acceptor would reduce the degree of order of P3HT leading to lower field-effect mobilities. [137,[142][143][144] Huettner et al synthesized a diblock copolymer consisting of poly(perylene bisimide acrylate) and PS.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…Previous work on molecular donor-acceptor materials produced only modest power conversion efficiencies, a result attributed to a loss of charge carriers to recombination within the overly small domains. 16 Although there has been extensive work on block copolymers (BCPs) that employ pendant chromophores on a nonconjugated backbone, [17][18][19][20][21] to maximize chromophore density, the polymers should be fully conjugated. For these reasons, fully conjugated BCPs are the subject of this investigation.…”
Section: Introductionmentioning
confidence: 99%